THE INFLUENCE OF PROCESS PARAMETERS TOWARD COLLAR HEIGHT ON INCREMENTAL BACKWARD HOLE-FLANGING PROCESS - Muhammad Fakhruddin; Mochammad Agus Choiron; Anindito Purnowidodo (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2017)
Abstract                  The experimental study of the influence of process parameters towards collar height on incremental backward hole-flanging (IBHF) process with aluminium plate workpiece was presented in this paper. The effect of process parameters toward collar height which produced by IBHF process was investigated. Experiments were performed with a CNC machine, a 30o conical forming tool, and aluminium plates. The process parameters are feed speed with two levels, radial forming step size with three, and axial forming step size with three levels. Some parameters were kept constant, i.e., spindle speed, initial hole diameter, final hole diameter, and conical forming tool diameter. Digital Vernier caliper was used to measure the height of the collar. Experimental results of IBHF process have shown that the feed speed (vf) parameter has no effect toward collar height. Increased radial forming step size (Δx/y), increased the collar height also. Increased the axial forming step size (Δz) reduced the collar height. Keywords: hole-flanging, incremental sheet metal forming, incremental backward.